2018
DOI: 10.33225/ppc/18.12.84
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Nomophobia’s Prevalence and Its Impact on School Performance Among Adolescents in Morocco

Abstract: Social networks are a new form of addiction to technology and are beginning to take place in the moroccan society in the last decades, especially among children and adolescents. Furthermore the Nomophobia is a new form of addiction to new generations of mobile phones. Because of the importance of their speed spread and their influence on the person's future and interpersonal relationships, we conducted a study to calculate the degree of Nomophobia in adolescent population. It is through the establishment of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
(8 reference statements)
1
10
1
2
Order By: Relevance
“…The results of other studies among adolescents do not give a clear picture. Two research studies which included a somewhat wider age range compared to our research (11-18 and 13-20 years of age) found that the frequency of problematic use increased with the participants' age (López-Fernández et al, 2014;Öz, Arslantaş, Buğrul, Koyuncu, & Ünsal, 2015), while another study determined that the problematic use increased with age in middle school and the first grade of high school, but then decreased in higher grades of high school, which the authors attributed to greater school responsibilities of older students and preparations for final tests (Louragli, Ahami, Khadmaoui, Mammad, & Lamrani, 2018). By comparing participants 3-11 and 12-19 years of age, Csibi, Griffiths, Demetrovics, and Szabo (2019) found that the younger group of participants was more prone to problematic mobile phone use, but also to various conflicts (being reprimanded by adults for overusing mobile phones), mood swings and lower self-control.…”
Section: Discussioncontrasting
confidence: 57%
“…The results of other studies among adolescents do not give a clear picture. Two research studies which included a somewhat wider age range compared to our research (11-18 and 13-20 years of age) found that the frequency of problematic use increased with the participants' age (López-Fernández et al, 2014;Öz, Arslantaş, Buğrul, Koyuncu, & Ünsal, 2015), while another study determined that the problematic use increased with age in middle school and the first grade of high school, but then decreased in higher grades of high school, which the authors attributed to greater school responsibilities of older students and preparations for final tests (Louragli, Ahami, Khadmaoui, Mammad, & Lamrani, 2018). By comparing participants 3-11 and 12-19 years of age, Csibi, Griffiths, Demetrovics, and Szabo (2019) found that the younger group of participants was more prone to problematic mobile phone use, but also to various conflicts (being reprimanded by adults for overusing mobile phones), mood swings and lower self-control.…”
Section: Discussioncontrasting
confidence: 57%
“…The prevalence of physical inactivity and leisure-time sedentary behaviour in this study were similar to the global prevalence (85% physical inactivity and 30% sedentary behaviour), 26 higher than in a previous local study in Morocco, 9 and did not change over time. An increased use of mobile devices and the internet among adolescents 27 , 28 may have contributed to the continued high prevalence of sedentary behaviour in Morocco. However, the prevalence of walking or biking to school significantly increased in this survey from 2006 to 2010 and 2016, to almost 70% on any day of the week or 53.0% on 3–7 days a week, which is higher than the average in 27 Asia-Pacific countries (42.1%; ≥3 days/week).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study conducted by Ahmed et al (2019) with 157 physiotherapy students, a significant and negative relationship was found between academic performance and nomophobia. In a study conducted by Louragli et al (2018) with 541 adolescents, a reverse relationship was found between nomophobia and school performance, and it was concluded that the role of smartphones in this relationship was more effective than notebook computers. In a study carried out with the participation of 308 female students studying medicine in Pakistan (Aman et al, 2015), it has been reported that 81% of students change their daily routines after receiving a smartphone and 53% of their academic performance is negatively affected.…”
Section: şEkil 5 Katılımcıların Nomofobi Algılarını Tahmin Eden Tahmin Gözden Geçirilmiş Yapısal Model Ve Uyum Değerlerimentioning
confidence: 99%